Rational design of porous organic molecules (POMs) based on B-heterocyclic carbenes. Issue 2 (11th January 2021) - Zhang, Congjie; Tian, Zeqiong; Jia, Wenhong; Mo, Yirong
Abstract : We have theoretically obtained 36 porous organic molecules (POMs), three novel 2D covalent organic frameworks (COFs) and one metal–organic framework (MOF) based on the B-heterocyclic carbene (BHC) building blocks and –C≡C– and Ag–C≡C–Ag linkers. Abstract : We have rationally designed and computationally verified 36 porous organic molecules (POMs), 3 types of novel 2D covalent organic frameworks (COFs) and one kind of metal–organic framework (MOF) based on the B-heterocyclic carbene (BHC) building blocks associated with –C≡C– and Ag–C≡C–Ag linkers. The topologies of the POMs are notably different from those previously reported. More interestingly, the hexagon channels of POMs are almost regular hexagons though the edges of the hexagon channels are not exactly the same. Among POMs, those with apertures of 7.2, 11.5 and 16.1 Å are predicted to be stable. The infinite lattices of POMs result in 3 types of 2D COFs (COF-BHC- n, n = 1–3), whose symmetry is approximately hexagonal. The first electron spectra of the 36 POMs calculated with the TD-B3LYP/6-31G** method range from 325.0 to 482.0 nm and strongly depend on the structures and sizes. Thus, the proposed POMs might be potential optical materials due to the wide range of spectra. Further, one of the POMs (POM-25) can be used as polydentate ligands to form 1D layered complexes (C1 –C3 ) with Ag–C≡C–Ag linkers. The infinite lattices of C1 –C3 result in a kind of 1D MOF (MOF-BHC-1). Analyzing the lengths in C1 –C3 and MOF-BHC-1, as well as the Wiberg bond indices (WBIs) in C1 –C3, we found that MOF-BHC-1 contains plenty of planar tetracoordinate carbons (ptCs). Thus, we have introduced ptCs into the field of MOFs and developed a method for obtaining MOFs with new topologies from POMs.